IT Team Project Management Transformation Plan for TIC Company’s IT Division - Fauzan Aldiansyah; Raharjo, Teguh; Fitriani, Anita Nur (The Indonesian Journal of Computer Science, 2024)
Nowadays, organizations are increasingly reliant on information technology to maintain efficient and effective internal systems, stay competitive, and meet the evolving needs of their customers. However, organizations facing challenges often include delays in project delivery, difficulties in managing workflows, and issues with accurately tracking progress and performance. The Information Technology Division of one of the testing, inspection, and certification companies in Indonesia is responsible for application development but frequently encounters operational issues such as development delays, unaddressed requests, difficulties in tracking project timelines and completions, and unclear job description alignments. This study examines Waterfall, Kanban, and Scrum Agile methodologies through case studies and Design Science Research Methodology to address these issues. Scrum Agile, with its principles and practices, is selected as the preferred solution for resolving these recurring problems. The research proposes transitioning project management to Scrum Agile methods and demonstrates how these methods effectively address several existing challenges. This approach results in the development of a new system that implements Scrum Agile for project management within the department. This research can enhance the efficiency and effectiveness of application development and improve project visibility and control for the organization. Additionally, it provides learning through comparative analysis to identify appropriate new methods and systems based on the case study.